Peran gender diversity dewan perusahaan dalam menentukan kebijakan dividen di Indonesia - Nur Utomo, Mohamad; Kaujan, Kaujan; Syahran, Syahran; Samsul Ulum, Akhmad (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Dividend policy becomes very important especially with the presence of gender diversity on the company's board. This study aims to empirically examine the role of women's gender on the board of commissioners and the board of directors in determining dividend policy. The research sample uses companies that pay cash dividends listed on the Indonesia Stock Exchange in the 2015-2019 period. Data analysis using SEM-PLS method with WarpPLS 8.0 application. The results showed that the gender diversity of the board of commissioners had a negative effect on dividend policy. The results of the analysis show that the negative effect of the gender diversity of the board of commissioners on dividend policy is non-linear which has a U-curve pattern. Meanwhile, the gender diversity of the board of directors has a positive effect on dividend policy. In general, the research results are in line with the agency theory which uses an increase in dividend payments to reduce the occurrence of agency problems.